The last innovation in achalasia treatment; per-oral endoscopic myotomy - Aslan, Fatih; Akpınar, Zehra; Alper, Emrah; Atay, Aynur; Aslan Yurtlu, Derya; Çekiç, Cem; Bor, Serhat; Ünsal, Belkis (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Per-oral endoscopic myotomy (POEM) is a minimally invasive endoscopic treatment option for patients with achalasia and has been performed since 2010. It is less invasive than Heller myotomy and its use is spreading rapidly worldwide. We present our results of POEM that, to the best of our knowledge, are the first cases in Turkey. Materials and Methods: We enrolled patients between May 2014 and September 2014; 8 patients with achalasia whose complaints recurred after pneumatic balloon dilatation underwent POEM. The procedure was performed under general anesthesia at the endoscopy unit of the gastroenterology clinic. Demographic data was recorded before the procedure, and the results of the procedure were recorded prospectively. Results: The median age of the patients was 42.5 (30–72) years. Preoperative and postoperative median Eckardt scores were 10 (8-12) and 1 (0-2), respectively. The median total duration of the procedure was 101 (71-158) min, and the median myotomy length was 13.5 (10–16) cm. Postoperative oral intake started on median day 1 (1-2) and the length of hospital stay was 4 (3-6) days. In 2 patients, capnoperitoneum developed during the procedure and was treated with a Veress needle. Conclusion: POEM is a safe endoscopic treatment modality for patients with achalasia in centers that are experienced in advanced endoscopic techniques.